Creole Radical Feminist Transitional Justice: An exploration of Colombian feminism in the context of armed conflict (2018)
The signing of the peace agreements between the FARC-EP and the Colombian Government in late November 2016 has generated new prospects for peace in Colombia, opening the possibility of redressing the harm inflicted on Colombians by Colombians.